Effect Of Bt-Transgenic Cotton On Soil Biological Health (Applied Biological Research, 2012)
Bt cotton are plants that have been genetically modified to express the insecticidal proteins Cry 1 Ac from subspecies of the bacterium, Bacillus  thuringiensis israelensis (Bt), to control bollworm pest that feed on cotton.  There is a persistent environmental concern that transgenic Bt-crops  carry genes that have indirect undesirable effect tonatural and agro ecosystem function. We investigated the effect of Bt-cotton (with Cry 1 Ac gene) on several microbial and biochemical indicators in fields under sub humid tropical condition. Twenty five fields were selected in the  Vidarbha region, India, where Bt-cotton has been growing at least three  consecutive years and side by side field of non-transgenic cotton is  growing under clay to clay loam soil. Soil from a control (no-crop)  treatment was also included from each area to compare the extent of  adverse effect of Bt, if any. Samples were analyzed for actinobacteria,  fungi and nitrifiers population, biomass carbon (MBC), biomass nitrogen  (MBN), biomass phosphorus (MBP) and soil enzyme activities. The result  revealed a significant decline in actinobacteria (17%), bacterial (14%)  count as well as acid phosphatase (27%), phytase (18%), nitrogenase  (23%) and dehydrogenase (12%) activities in Bt cotton compared with  non-Bt cotton fields. Fungal and nitrifier counts, and esterase and  alkaline phosphatase activities were not affected by the introduction of  Bt-cotton in fields. However, significant decline between 8 and 9% in  MBC and MBN was noticed.
Keywords: Bt toxin; enzyme activities; microbial biomass; soil health; transgenic Bt-cotton; tropical sub-humid climate